Changing Pattern of the Species Composition of Ring Seine Landings - Edwin, Leela; C., Hridayanathan (Fishery Technology, 2025)
The changing pattern of species composition of ring seine landings is modelled with the help of the Markov chain model to interpret the observed changes and predict the status of dominance of major species. The species selected for the study were oil sardine, other sardines, anchovies, carangids and mackerel. The landings from gear other than ring seines and all gear together have also been analysed. The probability of oil sardine dominating the ring seine catch has come down and in the case of other gear, carangids tend to dominate.